Providing a Bidirectional Abstraction for Unidirectional Ad Hoc Networks - Ramasubramanian, Venugopalan; Chandra, Ranveer; Mosse, Daniel; Ramasubramanian, Rama (IEEE Infocom, 2002)
Several routing protocols for mobile ad hoc networks work efficiently only in bidirectional networks. Unidirectional links may exist in a real network due to variation in transmission power of different nodes, noise or other signal propagation phenomena, and heterogeneity in transmission hardware of nodes in the network. We introduce a sub-layer called Sub Routing Layer, SRL, between the network and the MAC layer to provide a bidirectional abstraction of the unidirectional network to the routing protocols. We present a scalable and efficient way to provide this abstraction by finding and maintaining multi-hop reverse routes to each unidirectional link. We simulate SRL and a modified version of AODV that uses SRL to route packets in unidirectional network. We observed that with SRL, the packet delivery of AODV in unidirectional networks increases substantially. Further our simulations indicate that reverse routes are often only a few hops long and hence the overhead of using SRL is very low.